The occurrence and safety evaluation of phthalic acid esters in Oasis agricultural soils of Xinjiang, China - Hejiang Liu; Xiuting Liu; Kai Wang; Xingwang Ma; Haihe Gao; Xuejun Liu; Changrong Yan (Ecotoxicology and Environmental Safety)
Soil pollution caused by plastic residues containing additives (e.g. phthalic acid esters (PAEs)) is ubiquitous and has become a global concern. However, the distribution, accumulation, and potential risks associated with PAEs in agricultural soils have not been fully explored. This study quantified the types, concentrations, and distribution patterns of common PAEs in 29 agricultural soil samples collected from the Xinjiang Oasis, China. The results indicated that no significant variation in PAE concentrations across the oasis farmlands in Xinjiang. The PAEs were predominantly concentrated in the topsoil layer (0–20 cm), with an average concentration of 102.3 μg/kg, with some migration observed to the deeper soil layer (20–40 cm). The most abundant PAEs detected were Di (2-ethylhexyl) phthalate (DEHP), diisobutyl phthalate (DIBP), and diethyl phthalate (DEP), which accounted for 49.82 %, 23.74 %, and 20.96 % of the total, respectively. Furthermore, the concentrations of all PAEs were below China's soil quality risk control standards, and the non-carcinogenic risks to both adults and children were below the current threshold, indicating relatively low risks to both the human health and the environment. These findings are crucial for understanding the presence and safety evaluation of PAEs in Xinjiang Oasis farmland, and they provide important reference data for managing and controlling PAE contamination in agricultural soils.